Determinants of neural tube defect among children at zewditu memorial hospital, addis ababa, ethiopia a case control study - Filmawit Aynalem Tesfay; Fekadu Bulte Aga; Girum Sebsibie Teshome (Elsevier, 2021)
Background: Neural tube defects are one of the most common malformations with a worldwide prevalence of 1-3 per1000 live births. They are the result of failure of the neural tube to close during the 21-28 embryonic days and it had multi-factorial etiology. Objective: The aim of this study was to assess the determinants of neural tube defects at Zewditu Memorial hospital in Addis Ababa, Ethiopia. Method: A hospital based unmatched case control study was conducted with a ratio of 1:2 cases to control cases and a total of 60 cases and 120 controls were selected. Data was collected using a structured questionnaire. Data analysis was conducted using SPSS version 23 software. Results were summarized using descriptive statistics. Bivariate and multivariate logistic regression analyses were conducted for statistical testing. Statistical association was declared with p-value<0.05. Results: The results show that oral contraceptive use, young maternal age, parental low educational status, hot tub use, passive smoking, caffeine consumption of ≥ 3 cup/day, maternal occupation, family history of neural tube defects, maternal fever and being multiparous had an association with neural tube defects. In the multivariate analysis, maternal fever (OR 65.5 CI 4.4-957.9), family history of neural tube defects (OR 43.5 CI 1.2-1506.9), coffee consumption (OR 18.5 CI 3.7-91.1), antipyretic use (OR 0.01 CI 0.00 -0.53) and maternal age of < 19 (OR 33.3 CI 2.5-448.4) and 25-29 (OR 9.7 CI 1.3-67.6) had a significant association with neural tube defects. Conclusion: This study shows that maternal fever, family history of neural tube defects, coffee consumption, and young maternal age were associated with the increasing the risk of neural tube defect whereas antipyretic drug use had a protective effect.